CONTENT ANALYSIS OF YOUTUBE VIDEOS AND COMPATIBILITY TO K-13 CURRICULUM OF THE 7TH-GRADE STUDENT (A Descriptive Study on the YouTube Channel 'Miss Nita') - Prana, Ryan Sevtio; Bunau, Eusabinus; Salam, Urai (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
'Miss Nita"™ as a YouTube channel provide many educational videos to teach English as a foreign language. It has many beneficial contents that teach young learners in middle and high school. However, not all of these educational videos are well-matched with the school curriculum, students"™ level, and the design quality is decent. The aims of this research are (1) to find out the content of YouTube videos whether it is compatible with the K-13 curriculum or not; (2) to find out the content of YouTube videos whether it is suitable for students' level or not; and (3) to find out if the quality of the video is sufficient or not. The subject of this research is the YouTube channel "˜Miss Nita"™. The object of this research is the three videos related to descriptive text. This study is a descriptive study. Observation techniques were used to gather the information from three videos. Content analysis was the analysis instrument. The finding denoted that the three videos showed moderate aptitude compatibility to curriculum K-13 and high aptitude compatibility to students"™ level, and their design is very good quality though there were a few errors and mistakes. From this finding, it is concluded that the three videos from "˜Miss Nita"™ are very good educational videos and they could be used to teach 7th-grade students.